Assessing capacity to engage in healthcare to improve the patient experience through health information technology - Cynthia Sieck; Daniel Walker; Megan Gregory; Naleef Fareed; Jennifer Hefner (Patient Experience Journal, 2019)
Patient engagement is viewed as a means to improve patient care, increase population health, and decrease health care costs. Efforts to improve engagement are prevalent across healthcare, particularly through health information technology (HIT) tools such as patient portals. However, we know that not all patients have the same ability to engage, leading to potential disparities. We present the Engagement Capacity Framework and suggest that examining capacity for engagement would improve our ability to address currently unmeasured factors that facilitate engagement. The objective was to examine factors that influence an individual’s capacity for engagement through HIT. We administered a paper survey to patients seen for care in a Family Medicine Clinic at a large Academic Medical Center, measuring potential components of the Engagement Capacity Framework. 142 patients completed the survey. Respondents reported high self-efficacy, high resilience, and good or better quality of life. Most were willing to use the Internet. Almost 30% of respondents did not use a patient portal and 37% of these respondents were very or somewhat unwilling to use a portal. We observed significant positive correlations (p > 0.05) between portal use and searching for health information online, using email and owning technology. For those who did not use a portal we asked about willingness to use a portal; portal willingness was positively correlated with willingness to use the Internet (p < 0.01). Our findings emphasize the importance of assessing capacity for engagement in order to target interventions to those most in need, connecting them to necessary resources to allow more full participation in their care. Experience Framework This article is associated with the Innovation & Technology lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Innovation%20%26%20Technology%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens